Carbon nanotubes effects on the relaxation properties and critical current densities of MgB 2 superconductor - Pasquini, G. (2013)
Addition of nonsuperconducting phases, such as carbon nanotubes, can modify the superconducting properties of MgB 2 samples, improving the critical current density and upper critical field. A full understanding of the flux creep mechanism involved is crucial to the development of superconducting magnets in persistent mode, one of the main thrusts for the development of MgB 2 wires. In this paper we present a creep study in bulk MgB 2 samples, pure and with different amounts of carbon nanotubes additions. We conclude that the most consistent picture at low temperatures is a single vortex pinning regime, where the correlation length is limited by the grain size. We introduce a novel analysis that allows us to identify the region where the Anderson-Kim model is valid. © 2013 AIP Publishing LLC.